(untitled) (Medico Legal Update, 2021)
Background: Determining the sperm quality can be measured by calculating sperm motility and sperm motility is governed by intracellular calcium (Ca2+) concentration. However, the intracellular calcium increase found in essential hypertension cases may decrease acrosome reaction and increase ROS production, and may trigger sperm cell apoptosis. Ground cherry (Physalis angulata L) is an herbal plant containing bioflavonoid as antioxidant which is crucial to defend against free radicals and prevent toxic effects. Objective: This study aims to test the capacity of Physalis angulata L. extract, in preventing disruption of sperm motility in male Wistar strain rats model of hypertension through oxidative stress reduction and cytosolic calcium regulation. Method: Experimental animal male white rat (Rattus novergicus) model of hypertension were intraperitoneally inducted with L-NAME. The animals were divided into 5 treatment groups and given Physalis angulata L. leaf water extract with various doses for 14 consecutive days. At the end of the study, animals were sacrificed, and testes were taken for measuring the MDA levels, intracellular calcium, and sperm motility. Results: Physalis angulata L. leaf water extract is proven to prevent increasing number of testicular MDA level, prevent increasing number of sperm intracellular calcium, and prevent decreasing number of motile sperm in male white Wistar strain rat model of hypertension. Conclusion: The results show that the Physalis angulata L. leaf water extract is proven to prevent the increase of MDA testis level and the increase of intracellular calcium testis amount, and prevent the number of motile sperm on male Wistar strain white mice model of hypertension.